A case study on retrofit design for energy saving - Kincay, O; Bolat, E (UNIVERSITY TWENTE FACULTY EDUC SCI & TECHNOL, 2000)
In this work, the separation by distillation of dimethylacetamide - water mixture processed in a textile factory was studied and a process flowsheet was proposed to minimize the energy consumption of this operation accomplished to obtain 99.9% high purity products. The number, sequence and operation conditions of distillation columns, the heat duties of condensers and reboilers, the stream matching by heat integration and the properties of all process and utility streams were calculated and given as process characteristics. Comparing the proposed retrofit system with the initial system, the amount of energy saved by integration and the change in capital cost of heat transfer equipment were calculated. Also, the relationship of present worth of annual total energy cost savings with increase in annual energy cost and operating time was shown.
Keywords: Thermodynamics; Energy & Fuels; Engineering